2021
DOI: 10.1111/ijfs.15060
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to improve the nutritional value of meat products: incorporation of bioactive compounds, reduction or elimination of harmful components and alternative technologies

Abstract: Meat is an excellent source of protein with a good balance of amino acids. It is also rich in several minerals, vitamins and bioactive compounds, which play important roles in metabolism and are easily assimilated from meat compared with other foods. The nutritional value of meat is one of the factors that influence consumer acceptance. However, it can be significantly reduced during processing. Moreover, some operations, such as curing, smoking or fermentation, used for processing can lead to the formation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 88 publications
0
14
0
Order By: Relevance
“…Overall, it is meat with a relatively low energy value; a high level of wholesome, easily digestible total protein; and low fat and cholesterol content [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]; with a good fatty acid composition and n -6 to n -3 ratio (lower or close to 4) [ 4 , 7 , 8 , 15 , 17 , 18 , 19 , 20 , 21 ]. In addition, it has good healthy lipid indices such as the atherogenic index (AI) and thrombogenic index (TI) [ 15 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, it is meat with a relatively low energy value; a high level of wholesome, easily digestible total protein; and low fat and cholesterol content [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]; with a good fatty acid composition and n -6 to n -3 ratio (lower or close to 4) [ 4 , 7 , 8 , 15 , 17 , 18 , 19 , 20 , 21 ]. In addition, it has good healthy lipid indices such as the atherogenic index (AI) and thrombogenic index (TI) [ 15 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has good healthy lipid indices such as the atherogenic index (AI) and thrombogenic index (TI) [ 15 , 21 ]. It has been shown that the amounts of essential amino acids, vitamins (PP, B 1 , B 2 , B 6 , E) [ 7 , 13 ], micro- and macro elements (phosphorus, magnesium, iron, manganese, and zinc) [ 13 , 17 ] in game meat are much higher than in the meat from farm animals. Game can also be viewed as a source of bioactive compounds: among others, conjugated linoleic acid (CLA), as well as carnosine and anserine [ 22 , 23 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…An additional value for increasing their nutritional value may be reducing or eliminating synthetic additives, mainly nitrites, as well as the addition of plant additives which have antioxidant and health-promoting properties. These activities are part of strategies to improve the nutritional value of meat products [2]. The potential pro-health effects can be attractive for consumers as the demand for healthier foods has been growing in recent years [3].…”
Section: Introductionmentioning
confidence: 99%
“…The scope of this special issue is to disseminate high‐quality research related to new trends in strategies towards increasing the nutritional value of meat products and reviewing recent developments on the quality and safety improvement of functional meat products worldwide, such as the incorporation of bioactive components, reduction or elimination of harmful components (e.g. nitrite/nitrate, fat) (Cerón‐Guevara et al ., 2021) and alternative technologies (ultrasound) (Karwowska et al ., 2021). This theme emphasises the importance of functional meat products in the consumer health as meat products constitute a significant share in the diet of modern man.…”
mentioning
confidence: 99%
“…This theme emphasises the importance of functional meat products in the consumer health as meat products constitute a significant share in the diet of modern man. Articles published in this special issue covered a wide and interesting range of topics including the use of natural antioxidants to meat products, the use of fat substitute, the quality of dry‐cured meat products from deer loin, nutritional value of meat products with reduced content of animal fat, the use of emulsion hydrogels in enhancing the nutritional properties of foal burgers, antioxidant activity of peptides from dry‐cured pork loins, effect of nitrate reduction on biogenic amines and amino acids in traditionally produced dry fermented loins (Cerón‐Guevara et al ., 2021; Cittadini et al ., 2021; Karwowska et al ., 2021; Kęska & Stadnik, 2021; Vargas‐Ramella et al ., 2021).…”
mentioning
confidence: 99%